Within-Subject Comparison of Maxillary Implant-Supported Overdentures with and without Palatal Coverage - Zembic, Anja; Tahmaseb, Ali; Wismeijer, Daniel (Clinical implant dentistry and related research, 2015)
Purpose The purpose of this study was to compare patient‐reported outcomes for maxillary implant‐supported overdentures with and without palatal coverage. Materials and Methods Twenty‐one maxillary edentulous patients (six women, 15 men) were included. In total, 42 implants were inserted in the anterior maxilla. All patients received implant‐supported overdentures on two retentive anchors with palatal coverage for 2 months. Thereafter, patient satisfaction was assessed by means of questionnaires capturing the oral health impact profile (OHIP) on functional limitation, physical pain, psychological discomfort, physical, psychological and social disability, and handicap. Additionally, cleaning ability, general satisfaction, speech, comfort, esthetics, stability, and chewing ability were rated. Subsequently, palatal coverage was reduced, and the patients wore the overdentures for another 2 months. Patient satisfaction was obtained in the same way as above, and the evaluated parameters were compared for the two overdenture designs. Results There were no significant differences between implant‐supported overdentures with and without palatal coverage for any of the OHIP domains. The evaluation of additional parameters revealed significantly higher patient satisfaction for esthetics (mean difference 8.8 mm ± 24.6) and taste (mean difference 28.4 mm ± 29.9) without palatal coverage, p < .01. Conclusions Within the limits of this study, maxillary overdentures supported by two implants were equally satisfactory with and without palatal coverage.